2022
DOI: 10.1007/s00125-022-05715-4
|View full text |Cite
|
Sign up to set email alerts
|

Management of type 2 diabetes with the dual GIP/GLP-1 receptor agonist tirzepatide: a systematic review and meta-analysis

Abstract: Aims/hypothesis Tirzepatide is a novel dual glucose-dependent insulinotropic peptide (GIP) and glucagon-like peptide-1 receptor agonist (GLP-1 RA) currently under review for marketing approval. Individual trials have assessed the clinical profile of tirzepatide vs different comparators. We conducted a systematic review and meta-analysis to assess the efficacy and safety of tirzepatide for type 2 diabetes. Methods We searched PubMed, Embase, Cochrane and Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
4
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(152 citation statements)
references
References 30 publications
11
127
4
10
Order By: Relevance
“…Previous meta-analyses have shown that TZP is significantly more effective than GLP-1RA and insulin in lowering glycemia and reducing weight, and does not increase total AEs or cardiovascular risk ( 14 , 53 ), promising a new strategy for the treatment of T2DM. Meta-analyses published by Karagiannis et al ( 20 ) and Bhagavathula et al ( 21 ) comparing the efficacy and safety of TZP with placebo, insulin and GLP-1 RA for the treatment of T2DM confirmed that TZP was significantly more effective in lowering glycemia than placebo, insulin and GLP-1RA. Six clinical studies and a sample size of 4,358 were included in this meta-analysis and TSA, which is the first publication so far to study different doses of TZP in the treatment of T2DM.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous meta-analyses have shown that TZP is significantly more effective than GLP-1RA and insulin in lowering glycemia and reducing weight, and does not increase total AEs or cardiovascular risk ( 14 , 53 ), promising a new strategy for the treatment of T2DM. Meta-analyses published by Karagiannis et al ( 20 ) and Bhagavathula et al ( 21 ) comparing the efficacy and safety of TZP with placebo, insulin and GLP-1 RA for the treatment of T2DM confirmed that TZP was significantly more effective in lowering glycemia than placebo, insulin and GLP-1RA. Six clinical studies and a sample size of 4,358 were included in this meta-analysis and TSA, which is the first publication so far to study different doses of TZP in the treatment of T2DM.…”
Section: Discussionmentioning
confidence: 91%
“…TZP has been reported to lower glycemia and reduce weight significantly better than insulin and GLP-1RA ( 14 ), with the additional benefit of decreasing metabolites such as triglycerides and lipoproteins ( 19 ), and is expected to be a preferred strategy for the treatment of T2DM. The meta-analyses published by Karagiannis et al ( 20 ) and Bhagavathula et al ( 21 ) compared the efficacy and safety of TZP with placebo, insulin and GLP-1 RA in the treatment of T2DM, which confirmed that the hypoglycemic effect of TZP was significantly better than that of placebo, insulin and GLP-1RA. Unfortunately, they did not make an internal comparison of different doses of TZP, and it is unclear the optimal dose and dose adjustment strategy of TZP for the treatment of T2DM.…”
Section: Introductionmentioning
confidence: 83%
“…It has impressive glycemic efficacy. Moreover, it is the first effective drug to have demonstrated notable body weight loss in a phase 3 study in patients with T2D [38][39][40]. Tirzepatide has significantly better therapeutic efficacy than current drugs [20,41].…”
Section: Structure and Activitymentioning
confidence: 99%
“…Some other additional effects of tirzepatide were noted to lowering of the concentrations of very low-density lipoproteins and triglycerides, in addition to a reduction in blood pressure, as well as an elevation in high-density lipoprotein concentration. The adverse events most commonly reported were nausea, vomiting, and diarrhea, which were mild to moderate and occurred mostly during the dose-escalation period [40,54]. Further, in a phase 2 human clinical study with tirzepatide in conjunction with regulated nutrition and lifestyle The LPPS portion of the synthesis consisted of four steps and was carried out in a plug-flow reactor (PFR) [50].…”
Section: Clinical Developmentmentioning
confidence: 99%
“…Tirzepatide is a novel, once-weekly, injectable, dual glucose-dependent insulinotropic polypeptide (GIP) and GLP-1 RA, is being developed for the treatment of type 2 diabetes (T2D) and obesity [ 26 ] with CV safety demonstrated in the late phase clinical program [ 27 , 28 ]. The ‘Effect of Tirzepatide versus Dulaglutide on Major Adverse Cardiovascular Events (MACE) in Patients with Type 2 Diabetes (SURPASS CVOT)’ trial is the first trial designed to evaluate the CV efficacy of a novel antihyperglycemic medication for T2DM compared with a blinded active comparator with proven, product labeled CV efficacy, dulaglutide.…”
Section: Introductionmentioning
confidence: 99%